Changes in angiotensin-converting enzyme activity in lungs damaged by the pyrrolizidine alkaloid monocrotaline. - Lafranconi, W M (1983)
Administration of monocrotaline, a pyrrolizidine alkaloid, to male Sprague-Dawley rats for up to three weeks increased dry lung weights by 64% and reduced the specific activity of lung angiotensin-converting enzyme activity by 64%. When the total activity per lung is calculated, however, there is no significant difference between control and monocrotaline-treated animals. The decrease in specific activity is due to increase in total lung protein (52% above control) and not to an actual reduction in the total angiotensin-converting enzyme activity in th lung.